Possibilities of using agricultural biogas for the production of engine fuel - Samson-Bręk, Izabela; Biernat, Krzysztof (Studia Ecologiae et Bioethicae, 2009)
Agricultural biogas production and its applications are some of the most favorable methods of receiving the energy at present. Thanks to using biogas both to the production of electricity and the warmth and as an engine fuel we can limiting consuming nonrenewable energy sources. Using biogas as a fuel contributing also to the reduction of the greenhouse effect mainly thanks to methane reduction.